Aspects of Screening and Confinement in a Topologically Massive U1W×U(1)Y Chern-Simons-Higgs Theory - Patricio Gaete; José A. Helayël-Neto (Advances in High Energy Physics)
By using the gauge-invariant but path-dependent variables formalism, we consider a recently proposed topologically massive U1W×U(1)Y Chern-Simons-Higgs theory in 2+1 dimensions. In particular, we inspect the impact of a Chern-Simons mixing term between two Abelian gauge fields on physical observables. We pursue our investigation by analyzing the model in two different situations. In the first case, where we integrate the massive excitation and consider an effective model for the massless field, we show that the interaction energy contains a linear term leading to the confinement of static charge probes along with a screening contribution. In the second situation, where the massless field can be exactly integrated with its constraint duly taken into account, the interesting feature is that the resulting effective model describes a purely screening phase, without any trace of a confining regime.